Ekonomi Islam dan Pembangunan Lembaga yang Inklusif: Menyongsong Keadilan Sosial Berkelanjutan dalam SDG 16 - Sodik, Gugun; Riantani, Suskim (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
The Sustainable Development Goals (SDGs), established by the United Nations, serve as a global framework for fostering a more equitable, peaceful, and sustainable world. Among the 17 goals, SDG 16 emphasizes the importance of peace, justice, and strong institutions, which form the foundation for inclusive and sustainable development. This research focuses on the role of SDG 16 from the perspective of Islamic economics, aiming to explore how the principles of Islamic economics—particularly those related to social justice, wealth distribution, and institutional strengthening—can contribute to achieving these objectives. In the context of Islamic economics, the goal of creating a just and peaceful society is rooted in values such as adl (justice), mizan (balance), and maslahah (public interest), which are central to Islamic policies and economic practices. Islamic economics emphasizes transparency, accountability, and the equitable management of resources, aligning closely with the principles outlined in SDG 16. Additionally, Islamic financial instruments, such as zakat, waqf, and other social funds, play a vital role in strengthening economic structures that promote social justice and community well-being. Using a qualitative approach and comparative analysis, this study examines the application of Islamic economic principles in the context of sustainable development, with a particular focus on Muslim-majority countries that have integrated Sharia-based values into their economic policies. The research also discusses the challenges and opportunities faced by these countries in effectively implementing SDG 16. The findings of this study suggest that the application of Islamic economic principles, which prioritize justice, fair distribution, and the strengthening of legal institutions, can serve as an effective solution for achieving peace, social justice, and strong institutions in these nations. Overall, the study concludes that Islamic economics not only provides a moral and ethical foundation for achieving SDG 16 but also offers practical approaches to addressing social injustice, economic inequality, and social-political instability. Therefore, the integration of Islamic economic principles into sustainable development policies becomes a strategic step toward creating a more just, peaceful, and sustainable world. Key Word: Sustainable Development Goals (SDGs). Peace, Justice, and Strong Institutions, Islamic Economics. Social Justice.